Remobilization of hematopoietic stem cells in healthy donors for allogeneic transplantation. Issue 9 (17th June 2016) - Fiala, Mark A.; Park, Soo; Slade, Michael; DiPersio, John F.; Stockerl‐Goldstein, Keith E.
Abstract : BACKGROUND: The need to repeat peripheral blood (PB) stem cell mobilization and collection in healthy donors arises infrequently but may be required due to insufficient initial collection, graft failure, or relapse of the recipient's disease. Little data exist on the efficacy of remobilization. Therefore, we retrospectively reviewed 18 years of remobilization records from healthy stem cell donors at our institution. STUDY DESIGN AND METHODS: We identified 62 healthy donors who underwent remobilization, a cohort of 30 mobilized and remobilized with cytokines and a cohort of 32 mobilized with a CXCR4 antagonist and remobilized with cytokines. For each cohort we compared the PB CD34+/L level, the number of CD34+ cells collected/kg (recipient weight), and the number of CD34+ cells/L collected on the first day of leukapheresis during initial mobilization and remobilization. RESULTS: Initial mobilization with cytokines was associated with reduced remobilization. The mean PB CD34/L level at initial mobilization was 69 × 10 6 compared to 37 × 10 6 at remobilization (p = 0.029). In contrast, initial mobilization with a CXCR4 antagonist was not associated with reduced remobilization. The mean PB CD34/L level at initial mobilization was 15 × 10 6 compared to 68 × 10 6 at remobilization (p < 0.001). In both cohorts, initial mobilization results were positively correlated with remobilization results but the interval between was not. CONCLUSIONS: This study suggests that poor remobilization yields may be due to decreased efficacy of cytokines after repeat exposure. The underlying mechanism of these findings remains unclear and further studies are needed.